2003
DOI: 10.1128/jvi.77.14.8009-8018.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding at a Conserved Threonine in Lentivirus Capsid Is Required for Virus Replication

Abstract: The N terminus of the capsid protein (CA) undergoes a considerable conformational change when the human immunodeficiency virus (HIV) protease cleaves it free from the Pr55Gag polyprotein. This rearrangement is thought to facilitate the establishment of specific CA-CA interactions that are required for the formation of the mature viral core. Substitution of amino acids that are critical for this refolding of the N terminus is generally detrimental to virus replication and mature virion core morphology. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
1
9
1
Order By: Relevance
“…We also observed an associated defect in the level of virus production in proviral plasmids that carried the T47A mutation as compared to WT viruses (Table 1). These observations are consistent with the previously reported phenotype associated with the CA T47A mutation in SIV (32).…”
Section: Vol 80 2006 Ctl Epitope Mutation Disrupts Viral Core Assemsupporting
confidence: 83%
See 1 more Smart Citation
“…We also observed an associated defect in the level of virus production in proviral plasmids that carried the T47A mutation as compared to WT viruses (Table 1). These observations are consistent with the previously reported phenotype associated with the CA T47A mutation in SIV (32).…”
Section: Vol 80 2006 Ctl Epitope Mutation Disrupts Viral Core Assemsupporting
confidence: 83%
“…This hairpin is important for triggering condensation of the core particle and dimerization of the CA monomers. The salt bridge needed for the formation of this hairpin requires stabilization by a hydrogen bond with the neighboring threonine in position 48 (Thr 48 ) (28,32,33). Importantly, the HIV-1 Thr 48 and Asp 51 residues are equivalent to Thr 47 and Asp 50 in the SIV CA, and these threonine and aspartate residues are present in positions 2 and 5 of the Mamu-A * 01-restricted Gag p11C, C-M epitope.…”
mentioning
confidence: 99%
“…While the present study showed that the T47I mutation significantly decreased Gag protein expression by a plasmid, we and others did not observe an associated defect in the level of virus production when using full-length provirus plasmids (data not shown) (29,33). This discordance in findings might be attributable to differences in the experimental systems used for these studies.…”
Section: Discussioncontrasting
confidence: 54%
“…In fact, recent studies have demonstrated that specific residues of this epitope are required for optimal viral replication (29,33). Therefore, structural constraints may limit SHIV-89.6P from mutating away from p11C, C-M-specific CTL recognition.…”
mentioning
confidence: 99%
“…The previously characterized clones of the 5Ј (p239SpSp5Ј) and 3Ј (p239SpE3Ј) halves of the SIVmac239 genome (AIDS Research and Reference Reagent Program) (34,47) were used to generate the full-length D(25)A PR SIVmac239 mutant exactly as described previously (49). The primers used to create this viral mutant made a (GAT3GCT) nucleotide substitution in codon 25 of the protease-encoding portion of pol.…”
Section: Methodsmentioning
confidence: 99%